2015
DOI: 10.1016/j.ijcard.2015.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Underuse and overuse of anticoagulation for atrial fibrillation: A study in Indigenous and non-Indigenous Australians

Abstract: Anticoagulation for AF is frequently not prescribed in accordance with guideline recommendations. Under-anticoagulation in those at high stroke risk, and over-anticoagulation in those at low risk, is common and more likely in Indigenous patients with AF. Improving adherence to guideline recommendations for anticoagulation in AF may reduce both ischaemic and haemorrhagic strokes in Indigenous and non-Indigenous Australians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Oral anticoagulants reduce the risk of ischaemic stroke and all‐cause mortality despite the increased risk of major bleeding, but data on their use by Aboriginal Australians are limited. One study found that more than 70% of Aboriginal patients with AF and CHA 2 DS 2 ‐VASc scores of 2 or more were not receiving oral anticoagulants . Warfarin was the main oral anticoagulant available during our study period, but adequate monitoring of patients’ international normalised ratio (INR) in rural and remote communities is difficult because of remoteness, limitations in service availability and culturally appropriate referral pathways, and family caring responsibilities.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Oral anticoagulants reduce the risk of ischaemic stroke and all‐cause mortality despite the increased risk of major bleeding, but data on their use by Aboriginal Australians are limited. One study found that more than 70% of Aboriginal patients with AF and CHA 2 DS 2 ‐VASc scores of 2 or more were not receiving oral anticoagulants . Warfarin was the main oral anticoagulant available during our study period, but adequate monitoring of patients’ international normalised ratio (INR) in rural and remote communities is difficult because of remoteness, limitations in service availability and culturally appropriate referral pathways, and family caring responsibilities.…”
Section: Discussionmentioning
confidence: 97%
“…One study found that more than 70% of Aboriginal patients with AF and CHA 2 DS 2 -VASc scores of 2 or more were not receiving oral anticoagulants. 9 Warfarin was the main oral anticoagulant available during our study period, but adequate monitoring of patients' international normalised ratio (INR) in rural and remote communities is difficult because of remoteness, limitations in service availability and culturally appropriate referral pathways, 26 and family caring responsibilities. Recent Australian guidelines recommend novel oral anticoagulants (NOACs) for Aboriginal people with non-valvular AF because they overcome many of the logistic and clinical barriers associated with warfarin.…”
Section: Reasons For the Differences In Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke risk calculators have not been specifically tested or adapted for Aboriginal and Torres Strait Islander peoples with non-rheumatic AF. Making the assumption that these calculators are applicable, one local audit suggested that Aboriginal and Torres Strait Islander patients at high risk of stroke are undertreated whereas low-risk patients are overtreated, in a similar fashion to the general population [325].…”
Section: Anticoagulation In Aboriginal and Torres Straitmentioning
confidence: 99%
“…In general, these decisions are guided by the CHA 2 DS 2 ‐VA (stroke risk) score, which includes points for people over 65 or over 75 years of age . As 76% of Indigenous patients with CHA 2 DS 2 ‐VA scores of 2 or more do not receive anticoagulation therapy, undertreatment is a major problem . There is little evidence supporting the applicability of CHA 2 DS 2 ‐VA thresholds to Aboriginal patients, and, given their higher stroke rates, younger Aboriginal patients with non‐valvular AF but CHA 2 DS 2 ‐VA scores below 2 might well benefit from anticoagulation therapy.…”
mentioning
confidence: 99%